Reconstructing the Qibla Change through Ibn Hajar Al-Asqalani’s Fath al-Bārī: A Historiographical Analysis - Annisa Nurfadilah; Ahmad Izzuddin; Eman Sulaiman (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2026)
This study reconstructs the chronology and historical context of the qibla change – the redirection of Muslim prayer from Baitul Maqdis to the Ka‘bah – through a rigorous textual analysis of Ibn Ḥajar al-‘Asqalānī’s hadith commentary, Fath al-Bārī. While previous Islamic historiography has rarely treated hadith commentaries as viable primary sources, this study addresses that gap. Employing a qualitative framework that integrates historical-hermeneutic analysis with an interpretive-historical approach, it examines Fath al-Bārī to produce a chronologically precise and contextually grounded account. To reconcile conflicting reports on the date of the change, Ibn Ḥajar applied al-jam’ wa al-tawfīq (compromise) by specifying the lunar count from Rabī‘ al-Awwal to Rajab, explaining the 16‑ versus 17‑month discrepancy through inclusive and exclusive calculations. He then used tarjīḥ (critical selection) based on sanad quality to establish mid‑Rajab of the second Hijri year as the definitive moment of transition. The research also illuminates the socio‑political climate of Madinah, including Muslim‑Jewish relations, the Companions’ role in transmitting the news, and the event’s impact on consolidating early Muslim identity. The study concludes that Fath al-Bārī functions not merely as hadith exegesis but as a significant historiographical document, offering a methodological model for integrating hadith scholarship with historical inquiry.